Double-layer energy transaction strategy of multi-microgrids and distribution network with leased shared energy storage - WANG Hui; WU Zuohui; LI Xin; ZOU Zhichao; ZHOU Kerui (Diance yu yibiao)
To solve the challenges of imbalanced distribution of benefits among various interested parties during the cooperative operation of multi-microgrids under the same distribution network. Additionally, it considers the high investment cost and low utilization rate of distributed energy storage within multi-microgrids, a hybrid game based coordinated optimization model of multi-microgrids and distribution network is proposed in this paper. Firstly, an energy transaction framework between multi-microgrids and distribution network operators, which incorporates leased shared energy storage, is developed. Secondly, a multi-objective optimization model is created for multi-microgrids leased shared energy storage, which is designed to mitigate fluctuations in its net load. Then, a hybrid master-slave-cooperative game model with embedded multi-microgrid member cooperative game for distribution network and multi-microgrid master-slave game is constructed. Based on Nash negotiation theory, the cooperative game model between microgrid alliances is decomposed into two sub-problems: the minimum operating cost of the alliance and the distribution of cooperative income. In profit allocation of microgrid alliance, an asymmetric Nash bargaining method is proposed that fairly distribute profits according to the contribution size of each member in providing energy. Finally, an improved particle swarm optimization algorithm combined with the alternating direction multiplier method is adopted to solve the hybrid game model. Simulation results show that the proposed strategy can effectively improve the profits of multi-microgrids and utilization rate of energy storage, and realizes fair distribution of cooperative profits among alliance members.